2018
DOI: 10.1177/0309364617728120
|View full text |Cite
|
Sign up to set email alerts
|

A modified walk-in system versus scheduled appointments in a secondary-care prosthetic and orthotic clinic

Abstract: Background:Waiting is common in health care, delays intervention, and has negative effects on satisfaction with services.Objectives:To evaluate effects of a modified walk-in system, where patients were invited consecutively from the waiting list to attend the clinic on a walk-in basis, on waiting times, services, and work environment.Study design:Parallel-group trial.Methods:In all, 1286 consecutive patients in need of shoe insoles were randomized to waiting lists for modified walk-in (n = 655) or a scheduled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 19 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…However, previous literature has shown that single injections of resources, without changes to service delivery, are unlikely to make a sustainable difference to waiting times [ 35 , 36 ]. STAT is also consistent with other waiting time initiatives that have advocated approaches combining one-off backlog reduction strategies followed by the implementation of patient flow interventions [ 21 , 24 ]. In the current trial, a comparison of mean waiting times for a small sample of consecutive patients entering the service immediately before and after the waitlist reduction strategies provides some indication of their impact.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, previous literature has shown that single injections of resources, without changes to service delivery, are unlikely to make a sustainable difference to waiting times [ 35 , 36 ]. STAT is also consistent with other waiting time initiatives that have advocated approaches combining one-off backlog reduction strategies followed by the implementation of patient flow interventions [ 21 , 24 ]. In the current trial, a comparison of mean waiting times for a small sample of consecutive patients entering the service immediately before and after the waitlist reduction strategies provides some indication of their impact.…”
Section: Discussionsupporting
confidence: 81%
“…Reductions in waiting time achieved with STAT also appear to be comparable with other patient flow initiatives reported in community outpatient settings, although direct comparison is difficult due to heterogeneity in the ways in which wait times are measured. For example, there was a 23% reduction in median waiting time for a prosthetics clinic through changing scheduling to a modified walk-in system, rather than scheduled appointments [ 24 ]; Lynch et al achieved a 70% reduction in the number of people on a waiting list for mental health services with an intervention that addressed the residual waitlist in combination with new approaches to treatment and triage [ 23 ]; and Maddison et al described a reduction in waiting time for musculoskeletal services despite an increase in referrals through creation of a back pain pathway [ 34 ]. In contrast to these studies that all described interventions developed specifically for the services in which they were conducted, the current trial provides evidence of a structured approach that can be used to reduce waiting time across a broad range of settings.…”
Section: Discussionmentioning
confidence: 99%
“…46 To address these potential disadvantages, we chose to test a modified walk-in (MWI) system, where patients in need of shoe insoles were invited consecutively from a waiting list to attend our prosthetic and orthotic clinic on a walk-in basis. 7 We found that an MWI system reduced median time from referral to the first appointment by 40 days (23%) compared to SA, without substantially worsening waiting times in the waiting room, service quality or work environment. However, 17% of those randomized to the MWI system did not attend the clinic, compared to 6% for SA.…”
Section: Introductionmentioning
confidence: 72%
“…9,10 Consequently, they do not readily explain why the non-attendance rate was higher with the MWI system than the SA system in our original study. 7 Two interpretations are possible. First, the reasons for not attending the MWI clinic and SA could be similar but expressed differently; for example, both MWI clinic visit and SA can be forgotten or postponed if in conflict with other commitments, but it is presumably easier to forget or postpone an MWI visit than an SA, as the person is not committed to attending on a specific day and time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation